WASHINGTON LUIS: A PROPAGANDA POLÍTICA QUE LEVOU UM PAULISTA DE MACAÉ/RJ À PRESIDÊNCIA DA REPÚBLICA Um estudo sobre O Estado de S. Paulo e o Correio da Manhã (de dezembro de 1925 a março de 1926) - Franco, Lincoln (2008)
The purpose of the research is to find out how the political advertising from Washington Luís in the electoral process of 1925/1926, was arranged and also how the coverage of this process was made by the newspapers "O Estado de S. Paulo" and "Correio da Manhã". Using the methodology of historical research and concepts of political advertising, it will be analysed how "O Paulista de Macaé/RJ" built his political and personal career as weel as his indication to highest political position in the Republic.(AU)